Health related quality of life, perceptions and experiences of female patients with Systemic Lupus Erythematosus in South Africa: exploring unmet needs using a mixed methods approach - Phuti, Angel (Department of Medicine, 2020)
Objective: Systemic Lupus Erythematosus (SLE) is a multi‐system disease that predominately affects women. Considering the lack of data on health related quality of life (HRQoL) especially in sub‐ Saharan Africa, we undertook a literature review on HRQoL of SLE patients in developing countries to collate the existing evidence and identify information gaps. A mixed methods qualitative and quantitative study of lived experiences of South African women with SLE was performed. Methods: A literature search was conducted on medical databases using MeSH terms pertaining to HRQoL amongst SLE patients in the developing or low income countries to identify articles published between January 1975 and February 2018. The main study included 25 consenting SLE patients attending two tertiary hospitals in Johannesburg and Cape Town. Individual in‐depth interviews, using a topic guide, were conducted and analysed using NVivo software. In addition, participants completed the Short Form‐36 (SF‐36), Functional Assessment Instrument (FAI) and functional assessment of chronic illness therapy (FACIT) for fatigue questionnaires. The questionnaires were analysed per each tool's scoring method and SPSS software was used to calculate mean, standard deviations and correlations. Results The review of 31 articles, from 11 countries indicated that SLE women have a poor general HRQoL. In addition, we found relationships between disease factors including disease activity, organ damage, functioning, and mental health. Poor socioeconomic status worsened SLE outcomes by limiting patients' access to health care and psychosocial services. In the main study, the majority (72.0%) were black Africans, unemployed (76.0%), with low formal educational level and singlehood status (72.0%). The mean (SD) mental and physical composite SF‐36 scores were poor (50.9 (22.1) and 49.1 (20.5) respectively), and 68.0% of women had FACIT scores of severe fatigue. The mean (SD) FAI was 1.33 (0.8), showing that activities of daily living (ADL) were performed with difficulty. Major themes expressed were fatigue, pain, impaired functioning, depression, pregnancy, aesthetic concerns and sexuality issues. Disease chronicity, fatigue and pain were described by many participants as ‘taking over life' and impacting on performing ADL and career opportunities contributing to indigence. Negative pregnancy outcomes were frequently exacerbated by poor sexual relationships and miscommunication between patient and health care workers. Lack of understanding of SLE by patients, community and family as well as suicidal ideations and depressive symptoms were expressed. Although the quantitative tools measured these aspects, they were unable to explore complexities such as limitations in job acquisition, suicidal ideations, disease understanding and support systems. Conclusion This study underscores the complex, chronic and challenging life experiences, often exacerbated by poverty, of SA women with SLE. Quantitative tools may be inadequate in capturing important aspects of HRQoL that emerged from the qualitive interviews. Awareness of these limitations, together with psycho‐social support and education, might improve HRQoL. This thesis recommends multi‐centred, interventional longitudinal studies that incorporate mixed methods and focus on strategies to improve the negative outcomes in SLE.